CORRELATION BETWEEN DIETARY PATTERN OF PATIENTS WITH TYPE 2 DIABETES MELLITUS AND BLOOD SUGAR LEVEL - Mita Agustina (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Diabetes mellitus (DM) is one of the degenerative diseases that require careful management. The complication of diabetes mellitus may attack all the limbs due to uncontrolled blood sugar levels in diabetic patients. Diet is the most important nutritional management in people with diabetes mellitus to maintain blood sugar after meals and during fasting to avoid the risk of complications of type 2 diabetes mellitus. Methods: This study was a cross sectional design involved 74 respondents drawn from 282 population of patients type 2 diabetes mellitus in Kitamura Pontinak Clinic in January to November 2014. Results: Of 74 respondents, 58 respondents or (78.4%) were males and 16 respondents or (21.6%) were females. Most of the respondents in this study were under regular diet, whereas the irregular ones were due to economic factors, and the inability to adhere to diet. The results of chi square statistic test showed there is a correlation between dietary diet pattern on blood sugar decrease with the significant level of p = 0.000. Conclusion: There was a correlation between dietary pattern and blood sugar decrease. The result of the gamma correlation test showed that the magnitude of the correlation between dietary pattern and blood sugar decrease was in moderate level with γ = 0.974.